BNT162b2 COVID-19 Vaccination and Its Effect on Blood Pressure - Toh Leong Tan; Sharifah Azura Salleh; Zuraidah Che Man; Michelle Hwee Peng Tan; Rashid Kader; Razman Jarmin (Medicina, 2022)
Background and Objectives: The objective of this study is to examine the effect of the BNT162b2 vaccine on systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and pulse pressure (PP) before and 15 min after two doses that were given 21 days apart. Materials and Methods: This active surveillance study of vaccine safety was conducted on 15 and 16 March (for the first dose) and 5 and 6 April (for the second dose) 2021 in an academic hospital. For both doses, SBP, DBP, MAP, and PP levels were measured before and 15 min after both doses were given to healthcare workers over the age of 18. The results of the study were based on measurements of the mean blood pressure (BP), the mean changes in BP, and the BP trends. Results: In total, 287 individuals received the vaccine. After the first dose, 25% (n = 72) of individuals had a decrease in DBP of at least 10 mmHg (mean DBP decrease: 15 mmHg, 95% CI: 14–17 mmHg), and after the second dose it was 12.5% (mean DBP decrease: 13 mmHg, 95% CI: 12–15 mmHg). After the first dose, 28.6% (n = 82) had a PP that was wider than 40 mmHg. After the first dose, 5.2% and 4.9% of the individuals experienced an increase or decrease in SBP, respectively, of more than 20 mmHg. After the second dose, the SBP of 11% (n = 32) decreased by at least 20 mmHg. Conclusions: Improved understanding of vaccine effects on BP may help address vaccine hesitancy in healthcare workers.